A proposal for learning probability in early-childhood education through board games (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article introduces an approach, based on board games, to uncertainty situations and probabilistic reasoning in the early childhood education. Several authors suggest that simple probability notions should be taught as early as with 3-6 years-old children. Therefore, some teaching and learning processes have been suggested, always with an informal and introductory nature and usually about the comprehension of specific terms, such as sure, impossible, or probably. Likewise, it is shown that the main obstacle in the probabilistic reasoning development is that real-world situations where the idea of chance is present do not offer good information to make the learning meaningful. With this approach, some board games are analyzed, where the optimum strategy is based in probabilistic reasoning and it is described an educational proposal for 3-6 years-old children as an exploratory study.
Keywords: Early Childhood Education; Mathematics Education; Mathematical literacy; Uncertainty situations; Probability